Prevalence of ocular diseases in patients with pulmonary tuberculosis and HIV infection (Ukrainian Journal of Ophthalmology, 2026)
Background: Given the high prevalence and rate of disability from ocular pathologies, it is clinically and socially important to determine their prevalence in patients with tuberculosis and HIV infection.Purpose: To determine the prevalence of ocular diseases in patients with tuberculosis and HIV infection.Materials and Methods: Medical records related to regular medical check-up of 212 patients with tuberculosis (including those co-infected with HIV) at the Odessa Region Tuberculosis Dispensary in the year 2015 were retrospectively analyzed.Results: Ocular involvement was found in 86 (40.5%) patients (52 (60.4%) men and 34 (39.5%) women; mean age, 32.43 ± 7.45 years). Out of them, 52 (60.4%) patients (70 eyes) had both pulmonary and lymph node tuberculosis, whereas 34 (39.6%) patients had both tuberculosis and HIV. Focal chorioretinitis, disseminated chorioretinitis, keratitis, optic neuritis, scleritis and iridocyclitis were found in 31.3%, 22.09%, 17.44%, 8.13%, 8.13%, and 12.79%, respectively, of patients.Conclusion: Given the high prevalence of ocular pathology in patients with tuberculosis and HIV, ophthalmologists should give special attention to them. Posterior segment disorders (focal or disseminated chorioretinitis or optic neuritis) accounted for a major portion (61.52%) of the burden of ocular pathology in these patients. The frequency of glaucoma and hemorrhagic complications (retinal periphlebitis or vasculitis) in HIV-positive tuberculosis patients were 7.5 times and 6 times, respectively, higher than those in non-HIV tuberculosis patients.
Keywords: tuberculosis; HIV infection; ocular diseases